Roots of African American violence: ethnocentrism, cultural diversity, and racism - Hawkins, Darnell F. (Lynne Rienner Publishers, 2017)
Exploring the roots of African American violence -- Looking back, moving forward: theories of race and crime -- Toward a theory of African American violence -- Science, ideology, and the study of ethnocentrism -- On the conceptual roots of ethnocentrism -- Boxed in: ethnocentrism and urban violence -- Old guards and newcomers: ethnocentric white America -- Melting pot blues: ethnocentric black America -- A tale of two cities: race and homicide in Chicago and St. Louis -- Public policy to prevent violence